A palaeomagnetic study of the Basal Gneiss Region and Jotun Nappe Complex, central-southern Scandinavian Caledonides - Piper, J. D. A.; Poppleton, T. J. (Geophysical Journal International, 1990)
In the southern sector of the Scandinavian Caledonides a metamorphic gneiss complex (the Basal Gneiss Region or BGR) underthrusts a nappe complex of Precambrian granulites (the Jotun Nappe) in an assemblage collectively recording orogenic events culminating in the Scandian (Upper Silurian and Lower Devonian) episode. Palaeomagnetic study of a large regional sample spanning the combined outcrop identifies properties strongly controlled by metamorphic retrogression to amphibolite and greenschist facies. Low blocking temperature (Ibt) components in the BGR have E+ directions with a mean of D = 69° I = 60° ( N = 19 sites, α 95 = 7.0°); sporadic higher blocking temperature components define a dual polarity northeast negative/southwest positive (NE-/SW+) axis with a mean of D = 42°, I = -24° (20 sites, α 95 = 8.1°). Granulite facies rocks in the Jotun Nappe yield a high-quality palaeomagnetic record reflected in high Q n values and dominated by medium and high blocking temperature (hbt) components. A dual polarity (‘A’) axis defines a palaeofield migration from NE+ to E+ during uplift and cooling of this terrane with a predominance of normal polarities. A smaller population of lbt (‘B’) components show E+ directions distributed along the Mesozoic palaeofield migration path for Eurasia, and probably acquired during brittle tectonic events of this age. ‘A’ magnetizations from 86 sites define mean south pole positions between 301°E, 2°N and 325°E, 10°S linked to uplift-related cooling following the climactic Scandian orogenic episode and dated at 420-400 Ma from the collective geological and radiometric evidence. Both the outward and return segments of an APW loop may be represented. The polar swathe correlates with (i) a higher blocking temperature component from the BGR, (ii) the uplift magnetization record in the western orthotectonic Caledonides of Scotland, and (iii) primary magnetizations from the Siluro-Devonian molasse facies in Britain. This study shows that the westerly extension of the APW path identified by ...